Parole, Sintagmatik, dan Paradigmatik Motif Batik Mega Mendung - Nababan, Rudi -; Hendriyana, Husen - (PANGGUNG, 2012)
ABSTRACTÃÂ Discussing traditional batik is related a lot to the organization system of fine arts element ac- companying it, either the pattern of the motif or the technique of the making. In this case, the motif of Mega Mendung Cirebon certainly has patterns and rules which are traditionally different from the other motifs in other areas.Through ÃÂ semiotics analysis especially with Saussure and Pierce concept, it can be traced that batik with Cirebon motif, in this case Mega Mendung motif, has parole and langue system, as unique fine arts language in batik, and structure of visual syntagmatic and paradigmatic. In the context of batik motif as fine arts language, it is surely related to sign system as symbol and icon.ÃÂ ÃÂ ÃÂ Keywords: visual semiotic, CirebonÃ¢â¬â¢s batik.ÃÂ